Design and build a Microsoft product or software for Microsoft Imagine Cup 2018 (C) : integrated elderly care system - Fong, Thomas Guo Zhen (2018)
This project aims to develop a complete integrated elderly care system to assist caregivers in monitoring the physical well-being of an elderly living alone at home. The integrated system involves a mobile application which allows a network of caregivers registered to care for an elderly to receive immediate notifications for activation of help from the elderly or when abnormalities are detected using Microsoft Azure Cognitive services. A small computer (Raspberry Pi) equipped with camera and microphone is used as a sensor and a remote controller in the elderly home to capture events of interest, to trigger the notifications to be sent to the mobile application and to control access to the home. With the integrated elderly care system in place, caregivers will be able to receive time critical notifications of any help required by the elderly and act accordingly in a timely manner to immediately dispatch help to the elderly.